Relationship of Family Experience with the Acceptance of Family Members Who Have Mental Disorders - Aszrul AB; Fatmawati; Fitria Syam (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
Mental disorders are disorders that affect one or more functions of the soul that are characterized by disruption of emotions, thought processes, behaviors, and perceptions (sensory capture). This mental disorder causes stress and suffering for sufferers and their families. The family is the closest unit to a family member who has a mental disorder and is the